Ernest Ryland

## Answered question

2021-12-15

All the real zeros of the given polynomial are integers. Find the zeros, and write the polynomial in factored form.
$P\left(x\right)={x}^{3}+3{x}^{2}-4$

### Answer & Explanation

jean2098

Beginner2021-12-16Added 38 answers

Step 1
Given: All the real zeros of the given polynomial are integers.
Find the zeros, and write the polynomial in factored form.
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
Step 2
To Find the zeros, and write the polynomial in factored form:
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$=\left(x-1\right){\left(x+2\right)}^{2}$
=(x-1)(x+2)(x+2)
Therefore, The zeros of P(x) is P(x)=0
Hence, (x-1)(x+2)(x+2)=0
$⇒x=1,-2,-2$

Lynne Trussell

Beginner2021-12-17Added 32 answers

Consider the polynomial function in the textbook.
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
The objective of the questions is to find the zeros and write the polynomial in factored form.
Consider $P\left(x\right)={x}^{3}+3{x}^{2}-4$,
The leading coefficient is 1 and the constant term is -4, any rational zero must be a divisior of the constant term -4.
So, the possible rational zeros are $±1,±2$ and $±4$
Test each of these possibilities.
Let x=1
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(1\right)={\left(1\right)}^{3}+3{\left(1\right)}^{2}-4$
=1+3-4
=0
Now test for x=-1
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(-1\right)={\left(-1\right)}^{3}+3\left(-1\right)-4$
=-1+3-4
=-2
Similarly, for x=2
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(2\right)={\left(2\right)}^{3}+3{\left(2\right)}^{2}-4$
=8+12-4
=16
Similarly, for x=-2
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(-2\right)={\left(-2\right)}^{3}+3{\left(-2\right)}^{2}-4$
=-8+12-4
=0
Similarly, for x=4
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(4\right)={4}^{3}+3{\left(4\right)}^{2}-4$
=64+48-4
=108
Similarly, for x=-4
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(-4\right)={\left(-4\right)}^{3}+3{\left(-4\right)}^{2}-4$
=-64-48-4
=-116
Hence, real zeros of $P\left(x\right)={x}^{3}+3{x}^{2}-4$ are 1 and -2.
Now find the factored form of $P\left(x\right)={x}^{3}+3{x}^{2}-4$,
$P\left(x\right)={x}^{3}+3{x}^{2}-4$
$P\left(x\right)={\left(x+2\right)}^{2}\left(x-1\right)$
Hence, the factored form of $P\left(x\right)={x}^{3}+3{x}^{2}-4$ is ${\left(x+2\right)}^{2}\left(x-1\right)$.

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?